Hydrogenase Measurement with Photochemically Reduced Methyl Viologen - Yu, L. (1969)
Methyl viologen was reduced photochemically in the presence of proflavine and ethylenediaminetetraacetic acid. The reduced methyl viologen was oxidized by hydrogenase from Vibrio succinogenes. H(2) and oxidized methyl viologen were the products. Hydrogenase activity was determined by spectrophotometric measurement of the disappearance of reduced methyl viologen at 600 nm. The extinction coefficient of reduced methyl viologen was determined and is 8.25 mm(−1) × cm(−1) at 600 nm. Optimal conditions for assaying V. succinogenes hydrogenase were developed. Extracts of Escherichia coli and Desulfovibrio desulfuricans catalyzed reduced methyl viologen oxidation in the assay system, whereas Azotobacter vinelandii extracts were inactive.